Quantitative assay for ciprofloxacin and enrofloxacin formulations - Saundria Moed; Mackenzie Hall; Norman Lee; Clarissa Prazeres da Costa; Ernst K Rødland; Atena I Shemirani; Katie Clifford; Darash Desai; Muhammad H Zaman (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Ciprofloxacin (cipro) is a broad-spectrum fluoroquinolone antibiotic active against both Gram-positive and Gram-negative bacteria. It is used extensively in both animals and humans due to its high bioavailability and the wide range of susceptible infections. However, the use of substandard (poor quality) and counterfeit formulations of cipro in low- and middle-income countries has contributed to an increased risk of treatment failure due to antimicrobial resistance (AMR). Poor quality medicines especially have been linked to AMR. Therefore, there is a pressing need to screen for quality of cipro in low-resource settings. # Methods We have addressed this need by developing a low-cost fluorescence assay capable of quantifying the amount of cipro in tablets. In this assay, cipro is dissolved in deionized water and mixed with palladium(II) and methyl cellulose. Upon addition of these reagents, quenching of cipro is observed and quantified. # Results We demonstrated our assay with three brands of cipro, quantifying the tablets to within 3% error of the gold-standard, high-performance liquid chromatography. We extended this assay to assess the quality of enrofloxacin (enro), another fluoroquinolone primarily used in veterinary medicine, within 5% error of the package indication. # Conclusions These assays can be used to assess the quality of cipro and enro tablets in the field and identify substandard tablets, potentially helping to remove those tablets from circulation and decrease acceleration of AMR to cipro and enro. These assays can be easily adapted to previously-developed portable microfluidic platforms capable of assessing medicine quality in the field.